A review on Skin care and renewal with a beauty mask - Prof.Pratibha Bhalerao; Mayuri Navnath Jangale; Balaji Suresh Jadhav; Deep Prakash Gulave (Recent Trends in Cosmetics, 2025)
An important part of aesthetics is skin health. For this purpose, researchers and skincare experts continuously develop innovative materials and advanced techniques. To maintain optimal skin health, facial cosmetics keep skin moisturized and help to eliminate sebum from the skin. Using cosmetics that are appropriate for the kind of skin on the face leads to good skin. Therefore, in this study, we developed a natural face pack using readily available ingredients for effective application. After testing, we discovered that the face packs were free of irritation for the skin and maintained their consistency even under stable storage conditions.The results of the study scientifically confirmed that the natural face pack has the ability to provide an effective glowing effect on the skin.The General Review Is Valuable To Validate Item Claims Due Its Helpful Advantages On The Human Creatures. Facial cosmetics help keep the skin hydrated and eliminate excess sebum, promoting optimal skin health. Using cosmetics tailored to one’s specific skin type contributes to maintaining healthy and radiant skin. Among these products, facial masks are the most commonly used for skin rejuvenation. They can be categorized into four types: (a) Sheet masks, (b) peel-off masks, (c) rinse-off masks, and (d) hydrogels—each providing distinct benefits tailored to different skin types based on their ingredients.
Keywords: Glowing; Irritancy; Natural face pack; Sheet masks; Skin